Impact of Serum Uric Acid Lowering and Contemporary Uric Acid-Lowering Therapies on Cardiovascular Outcomes: A Systematic Review and Meta-Analysis - Ying, Hangying; Yuan, Hongdi; Tang, Xiaomei; Guo, Wenpu; Jiang, Ruhong; Jiang, Chenyang (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study aimed to evaluate the potential association between uric acid (UA) lowering and cardiovascular risk reduction among UA-lowering therapies in adults. Methods: A systematic search for randomized controlled trials (RCTs) was conducted according to the protocol pre-registered in PROSPERO (No. CRD42020199259). We search for RCTs in PubMed, Embase, Web of Science, the Cochrane Library, and ClinicalTrials.gov up to July 1, 2020. A meta-analysis was performed using a fixed- or random-effects model. Results: In total, 30 studies involving 18,585 hyperuricaemic patients were included. Xanthine oxidase inhibitor (XOI) therapy produced a 6.0% reduction in relative risk (RR) for major adverse cardiovascular events (MACEs). The use of febuxostat was associated with a higher risk of cardiovascular events (CVEs) (RR: 1.09, 95% CI 0.998–1.19, I2 = 0.0%), but the difference was not statistically significant. Allopurinol treatment was associated with a lower CVE risk (RR: 0.61, 95% CI 0.46–0.80, I2 = 21.0%). Among the UA-lowering therapies, the drug treatments were associated with all-cause mortality (RR: 1.20, 95% CI 1.02–1.41, I2 = 0.0%). The subgroup with a UA endpoint <7 mg/dl was not associated with a higher CVE risk (RR: 0.57, 95% CI 0.35–0.92, I2 = 0.0%), and in the subgroup with a UA endpoint <5 mg/dl group, a lower risk of CVEs was not observed (RR: 0.99, 95% CI 0.69–1.44, I2 = 0.0%). Conclusions: UA reduction caused by XOIs reduced the incidence of MACEs. UA-lowering medicines were associated with changes in all-cause mortality but not cardiovascular outcomes. The lower UA endpoint was not associated with reduced cardiovascular risk.